The Teacher Education Conversation: A Network of Cooperating Teachers - Nielsen, Wendy S.; Triggs, Valerie; Clarke, Anthony; Collins, John (Canadian Journal of Education/Revue canadienne de l’éducation, 2010)
This study investigated a professional learning community of cooperating teachers and university‐based teacher educators. To examine our roles and perspectives as colleagues in teacher education, we drew on frameworks in teacher learning and complexity science. Monthly group meetings of this inquiry community were held over two school years in a suburban school district in British Columbia. Participants’ current and prior experiences in the role of cooperating teacher provided rich topics for conversation. Our analysis illustrates how aspects of complexity thinking both enable and promote teacher learning, in this instance, the professional development of cooperating teachers. The study highlights (a) key tensions that allow for deeper exploration of issues, (b) the need for flexibility that is open to contingency, (c) the importance of reducing hierarchical structures to enable networks to develop, and (d) improvisation as a key ingredient for teacher learning.